The roles of the universities in the national development of Malaysia - Robiah Sidin, (Universiti Kebangsaan Malaysia, 1980)
Universities in Malaysia have been identified as one of the leading agencies for national development. Like other government institutions universities have to orientate themselves towards meeting national development goals and objectives. Certain roles have been identified and rationalised for them by both academic and government officials.